Efektivitas Terapi Relaksasi Otot Progresif (PMR) Dan Terapi Spiritual Dzikir Terhadap Penurunan Tekanan Darah Pada Penderita Hipertensi - Sinus Agustina, Wahyu; Ikhlasul Amal, Ahmad; Melastuti, Erna; Dwi Retno Sulistyaningsih (STIKes Ibnu Sina Ajibarang, 2025)
This study was conducted to evaluate the effectiveness of Progressive Muscle Relaxation (PMR) therapy and spiritual dhikr therapy in reducing blood pressure in hypertensive patients, a condition known to cause various serious health issues. The study design adopted a quasi-experimental approach with a pretest-posttest method and a control group. A total of 36 participants were selected using purposive sampling techniques and divided into two groups: one group receiving PMR and dhikr therapy as treatment, and a control group receiving standard care. Blood pressure measurements were taken before and after the intervention. The study findings revealed a significant reduction in systolic and diastolic blood pressure in the intervention group compared to the control group (p<0.05). These results indicate that PMR and dhikr are effective non-pharmacological approaches for reducing blood pressure in hypertensive patients.